Zamierzone przyczynienie się do popełnienia zbrodni przez grupę osób działających we wspólnym celu. O wymiarze kary współmiernej do niesprawczej formy współdziałania przestępnego w międzynarodowym prawie karnym - Fraser, Aneta (Problemy Prawa Karnego, 2025)
The purpose of the article is to provide guidance in identifying the circumstances that the International Criminal Court (ICC) should consider when imposing the sentence for ‘in any other way contributing to the commission of a crime by a group of persons acting with a common purpose’, as provided for in Article 25(3)(d) of the Rome Statute. The proposed exemplary circumstances are not actus reus elements of the concept of joint criminal enterprise (JCE), however they relate to them. In other words, regardless to the fact that the concept of JCE has not been adopted by the ICC, it is concluded that the elements relating to such enterprises are relevant, to the extent indicated, for the application of Article 25(3)(d) of the Rome Statute.